Umur Dan Paritas Terhadap Kejadian Preeklamsi Berat Pada Ibu Hamil Di UGD Kebidanan: Age and Parity on the Incidence of Severe Preeclampsia in Pregnant Women in the Obstetric Emergency Room - Handayani, Elen Dwi (Chakra Brahmanda Lentera Institute, 2022)
Preeclampsia is the development of hypertension with proteinuria or edema or both caused by pregnancy or influenced by the current pregnancy. The Purpose To Determine the Relationship of Age and Parity to the incidence of severe preeclampsia in pregnant women at the Midwifery ED at Torabelo Hospital, Sigi, Central Sulawesi. The design used in the study was Crossectional. Population is all pregnant women. The sample size is 72 respondents using the Independent Variable Purposive sampling technique of research is age and parity. The dependent variable is Uterus contraction. Data was collected using a questionnaire, then the data were analyzed using logistic regression tests with a significance level of α ≤ 0.05. The results showed that most respondents had a age of 20-35 years as many as 44 respondents (61.1%), multipara parity as many as 43 respondents (59.7%), did not have a heavy preeclampsia as many as 64 respondents (88.9%). The results of statistical tests in this study indicate that, the significance value of the p value of the Wald test is 0,000, which means that each variable has a partial effect. The results of the statistical test with p <a and a value of <0.05, in the age variable found that (p) 0.123 which means thatAge does not affect the incidence of severe preeclampsia. The test results on the parity variable found that (p) 0.013 which means that parity affects the incidence of severe preeclampsia. There is a relationship between Age and Parity Against Severe Preeclampsia in Pregnant Women in Midwifery Emergency Unit at Torabelo Hospital, Sigi Regency, Central Sulawesi. Appropriate age andparity can prevent severe preeclampsia in the mother.